تأثيرات التعرض لاشعة اكس على بعض معايير وشكل خلايا دم طيور السمان المحلي - إسماعيل محمد الهمالي (The Libyan Journal of Science, 2023)
The aim of this study was to investigate the effects of X-ray radiation on some hematological parameters, morphology of red and white blood cells of common Quail. Adults quail exposed to radiation were divided into 3 groups according to period of exposure. 1.03 Gy,1.44 Gy and 0.0 Gy for an exposure period 30 minetes per day (7 days) using an irradiation device (RÖntgenegeräf 35 kv, Grundgerät, No: 09058.99). Fifteen healty of males Coturnix sp randomly distributed in three cages (5 birds per cage). The findings indicate that no effect on the level of Hb treated groups compared with the control group. however, there was an increase of HCT level in group exposured to high dose 1.44 Gy (P<0.05). While 1.03 and 1.44 of blood urea and uric acid and creatinen in serum birds of two treated groups. In addition to were high significantly (p=0.00) increase Na+ and K+ significantly increased by two irradiation doses, while Cl− reduced in serum of the birds treated. The results shows that X-ray effects on blood cells morphology espicially on RBC such as increased of echinocytosis, terminal nucleus, cell swelling and increased the number and aggregation of lymphocyt